Hypnoprenatal reduces anxiety and stress in high-risk pregnancy in North Tapanuli District - Sulastry Pakpahan; Ganda Agustina Hartati Simbolon; Elly Sianturi; Juana Linda Simbolon (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: High-risk pregnancies can cause more complications for the mother and fetus during pregnancy, childbirth, and the puerperium compared to normal pregnancies. High-risk factors during pregnancy can increase worry and stress, which can influence labor and delivery and are risk factors for postpartum depression. During pregnancy, stress can increase the risk of having a premature, low-birth-weight baby. Hypnoprenatal is an effective communication method to incorporate positive suggestions into the subconscious mind of pregnant women to reduce anxiety and stress during pregnancy. Objectives: to determine the effect of hypnoprenatal intervention on anxiety and stress in high-risk pregnant women in the North Tapanuli District. Methods: This research method used a pre-experimental method with a one group pre-test post-test design. Samples were taken by the purposive sampling method, which, based on the inclusion criteria, obtained as many as 36 high-risk pregnant women who experience anxiety and stress. Hypnoprenatal intervention was carried out for 3 days, twice a day, and then observations and interviews were carried out using the DAS 42 questionnaire. Data analysis used a paired t-test. The results showed that the characteristics of the respondents based on the age of the majority were >35 years (44.7%), secondary education (33.3%), farmer's work (52.8%), primigravidas (17%), high-risk pregnancies (72.7%), and low risk (27.8%).Results : The results of the statistical tests showed differences and decreased levels of anxiety and stress in pregnant women at risk before and after the hypnoprenatal intervention, with a p-value of 0.000 (p<0.05). Conclusions: hypnoprenatal has a significant effect on the level of anxiety and stress among pregnant women at risk. It is recommended that pregnant women use hypnoprenatal techniques to help reduce anxiety and stress during pregnancy, which affects the mother's psychological condition.